"A very risky queer thing to do": In conversation with Ken Plummer. (June 2023) - Stein, Arlene; Kong, Travis S. K.
A conversation about the different generational experiences of LGBT academics and the changing status of sexuality and queer studies. Ken Plummer, Arlene Stein and Travis Kong, longtime colleagues and sociologists of sexuality, share their insights. They discuss how different generational contexts and geographic locations shape sexuality studies. They acknowledge the ways Ken's work, and the efforts of his generation of activist-scholars, played a pivotal foundational role in establishing LGBT studies. They consider the relationship between queer theory and sociologies of homosexuality, and the growing importance of digital media. In conclusion, they discuss how neoliberalisation and authoritarian movements are impacting intellectual work.